Rationale and optimising of outcomes in high-intensity interval training for health and disease - Shigenori Ito (Japanese Society of Physical Fitness and Sports Medicine, 2021)
High-intensity interval training (HIIT) research has drastically increased globally in the last decade. This might be owing to the application of HIIT in various fields such as among cardiovascular disease and cancer populations, and its increasing popularity in the media and fitness industries. It is crucial to realize the substantial benefits of HIIT, keeping safety in mind, for these target groups. In this narrative review, HIIT is discussed from multifaceted perspectives. First, I describe the rationale behind the improvement in aerobic and metabolic capacity with HIIT requiring less time compared to moderate-intensity continuous training, as well as the enjoyable and affective factors and the broad applicability of HIIT due to the "relative" high-intensity training. Second, I describe ways to maximize the effects of HIIT, which include optimising a potential genetic factor in HIIT responder, decreasing non-responders by attaining a targeted intensity, and adhering to the exercise intensity and unsupervised long-term participation. Recent development of HIIT/sprint interval training protocols and several unique clinical studies in the world have helped overcome the barriers against high adherence. Finally, safety and potential risks were only discussed briefly due to insufficient available data. In conclusion, to utilise the benefits of HIIT effectively and safely for unfit subjects with lifestyle-related and chronic diseases, optimising HIIT protocols to include high adherence to exercise intensity and long-term participation should be considered.